ZERO WASTE DENGAN PENGOLAHAN SAMPAH BASAH RUMAH TANGGA MENJADI PUPUK ORGANIK DI DESA SETRAJAYA - Anggi Haerani; Raden Kania; Rohaelis nuaraisiah (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Daily activities on a household scale produce a large amount of waste. Garbage becomes a problem when its volume continues to increase without any processing effort. Household waste is one of the urgent problems in SetraJaya Village that needs to be resolved immediately. This has become one of the focus of work in community service activities carried focused lecturers with group 24 students at Banten Jaya University. This activity was carried out in a series of service activities for one month which took place in the SetraJaya village, koroncong Pandeglang. This training aimed to provide knowledge about household waste regarding the types, impacts, sorting, and processing and to teach simple technology for waste processing. The training was carried out in three stages, namely preparation, implementation, as well as evaluavbout participation in the training showed an increased awareness to protect the environment. Processing of organic waste produces organic fertilizers and natural pesticides. Household waste processing can overcome the problem of waste generated by the community as well as produce products that can be reused by the community. Waste that comes from the community can be used again by the community is one application of the concept of zero waste.